Diversity of hemodynamic types in connective tissue disease associated pulmonary hypertension: more than a subgroup of pulmonary arterial hypertension - Xingbei Dong; Yue Shi; Ying Xia; Xiao Zhang; Junyan Qian; Jiuliang Zhao; Jinmin Peng; Qian Wang; Li Weng; Mengtao Li; Bin Du; Xiaofeng Zeng (BMC Pulmonary Medicine, 2022)
Abstract Objective Connective tissue disease associated pulmonary hypertension (CTD-PH) is classified as a subgroup of WHO group 1 PH, also called pulmonary arterial hypertension (PAH). However, not all CTD-PH fit hemodynamic definition of PAH. This study investigates the diversity of hemodynamic types of CTD-PH, their differences in clinical characteristics and outcomes. Method We performed a retrospective cohort study. CTD-PH patients were enrolled and divided into WHO group1 PH, WHO group 2 PH and hyperdynamic PH (mPAP > 20 mmHg, PVR < 3WU, PAWP < 15 mmHg) according to hemodynamics obtained by right heart catheterization. Patients with severe lung diseases, heart failure with reduced ejection fraction, pulmonary embolism, and hepatic cirrhosis were excluded. Baseline characteristics, autoantibodies, cardiac function, echocardiogram parameters, hemodynamics and survival rates were compared. Result A total of 202 CTD-PH patients were included, 138 in WHO group 1 PH, 33 in WHO group 2 PH and 31 in hyperdynamic PH. We found hyperdynamic PH is less severe, presenting lower NT-proBNP level, better WHO function class, lower mPAP and PVR, higher cardiac output, and less cardiac remodeling. Incidence of anti-RNP was significantly lower in patients with elevated PAWP. Short-term survival was worse in WHO group 2 PH, yet 5-year survival rates didn’t differ between groups. Conclusion Considering diversity in hemodynamic types, CTD-PH is more than a subgroup of PAH. Different types of CTD-PH present different clinical phenotypes and outcome. Phenotyping PH in CTD-PH patients is important.